Measurement of mass attenuation coefficient and its derivable in polymers. (February 2022) - Nagaraja, N.; Sridhar, K.N.; Manjunatha, H.C.; Vidya, Y.S.; Seenappa, L.; Gupta, P.S. Damodara; Ramalingam, H.B.
Abstract: We have measured the mass attenuation coefficient (MAC) and its derivable such as linear attenuation coefficient ( μ ), half value layer (HVL), tenth value layer (TVL), free path ( λ ) and specific gamma ray constant ( Γ ) of some commonly used polymers (Polysterene, Polypropylene, PTFE, PVC, PCTFE, Technora, Zylon, Vectron, Mylar, Bekalite, Twaron and Orlon), Silicon polymers (Poly dimethyl siloxane, Polymethyl Hydro silaxane, Per hydro poly silaxane, Poly dimethyl silaxane, Methylsilses quioxane and Silalkalyene polymer), Co-ordination polymers (Lead monoclinic-(I), Lead monoclinic-(II), 2D Cadium co-ordination polymer, Azelato barium (II) polymer, 1-D Co-ordination barium polymer(I), Helical lead(II) Co-ordination polymer, Lead tetragonal, Calcium bromide polymer(I), Calcium bromide polymer(II) and 1D Cadmium co-ordination polymer), Boron polymers (Polyborazylene, 4- Vinylphenylboronic acid, Borazine, 3-Acrylamidophenylboronic acid, E-phenyl ethenyl boronic acid, 4-Aminophenylboronic acid and 3- Aminophenylboronic acid) and Lanthanide polymers (Lanthanum polymer, Cerium polymer, Praseodymium polymer, Gadolinium texaphyrin, Terbium co-ordination polymer and Erbium phosphate hydrate polymer) at different gamma energies such as 81, 276, 302.8, 356, 383.80, 511, 661.6, 835, 1173 and 1332 keV using various gamma sources such as Ba-133, Na-22, Cs-137, Mn-54, and Co-60. It is also observed that Lead tetragonal polymer is having larger μ / ρ and μ and smallest HVL and TVL. Thus, it can be concluded that the Lead tetragonal polymer is the best absorber of gamma radiation among all the investigated polymers. The measured data is tabulated and this can be considered standard data for polymers. The present work will be useful in the fields of Radiation Physics and shielding.